Examples and the facilitation of student learning: should instructors provide examples or should students generate their own?. Issue 3 (3rd July 2019) - Bolkan, San; Goodboy, Alan K.
ABSTRACT: This study examined learning differences for students who were given instructor-provided examples during a lesson compared with student-generated examples. In an experiment, 348 students were exposed to an online lesson about fear appeals and were randomly assigned to either a condition where (a) examples of key concepts were provided by the instructor, (b) students were asked to provide their own hypothetical examples of key concepts, or (c) students were asked to provide their own personal examples of key concepts. Data were analyzed to examine differences in students' test scores while controlling for the impact of their familiarity with the material and grade point averages. Results revealed that, compared with students exposed to instructor-provided examples, students who generated their own scored lower on a test of recall and application. This outcome was modeled using path analysis specifying a moderated serial mediation effect. Specifically, instructor-provided examples created higher lesson clarity for students which helped them organize the lesson material into a more coherent mental model and, subsequently, score higher on the test. The serial indirect effect of example type on learning occurred most prominently for students who were disinterested in the lesson material.